Reconstructing Lives: Emotional and Social Adaptation of Divorced Women in Lahore, Pakistan - Iftikhar, Sahar; Kainaat, Farah; Siddqiue, Muhammad Usman (Annals of Human and Social Sciences, 2023)
The current study delved into the impact of divorce on the social adjustment of women, recognizing divorce as a prevalent psychological event with widespread effects on individuals' lives. The hypothesis centered on divorced women encountering heightened emotional challenges and encountering more social issues compared to married women. Additionally, it postulated a correlation between emotional and social problems in women, with social support and socioeconomic status serving as potential predictors of these issues. Using a convenient sampling method, 60 females from distinct areas of Lahore—Cantt, Mughalpura, and Shalimar—were selected for the research. Several scales including the Depression, Anxiety and Stress Scale (DASS), loneliness Scale, Social Interaction Anxiety Scale (SIAS), State-Trait Anger Expression Inventory (STAXI), Multidimensional Scale of Perceived Social Support, and Socioeconomic Status Scale were utilized for data analysis. The study focused on divorced females residing in Lahore and employed a semi-structured interview schedule for assessment. Data analysis involved percentages and graphical representations. The findings revealed that divorced women experienced heightened levels of depression, anxiety, stress, loneliness, social interaction anxiety, and state anger. Specifically, the study aimed to explore the potential relationship between a divorcee's socioeconomic status and their social adjustment, encompassing factors such as income and education. Furthermore, it investigated the contributing factors leading to divorce in Pakistan and examined the societal status of divorced women.